1998
DOI: 10.3171/jns.1998.88.5.0874
|View full text |Cite
|
Sign up to set email alerts
|

The presence of 4-hydroxynonenal/protein complex as an indicator of oxidative stress after experimental spinal cord contusion in a rat model

Abstract: Data from this study indicate possible compromise of neuronal, axonal, glial, and synaptic function after trauma, which may be a factor in motor deficits seen in animals after spinal cord contusion. The colocalization of the IgG stain with the HNE/protein stain is consistent with the hypothesis of a mutual cause-effect relationship between BSCB and oxidative stress in central nervous system trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…The accumulation of protein-bound HNE, which was demonstrated by previous reports in rat spinal cord injury (8,9), was also evident in this guinea pig SCI model, in both the injury site (T10-T11) and adjacent segments (T8-T9 and T12-T13) (Fig. 2).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The accumulation of protein-bound HNE, which was demonstrated by previous reports in rat spinal cord injury (8,9), was also evident in this guinea pig SCI model, in both the injury site (T10-T11) and adjacent segments (T8-T9 and T12-T13) (Fig. 2).…”
Section: Resultssupporting
confidence: 63%
“…Therefore, these byproducts of lipid peroxidation have been postulated to be involved in the pathogenesis of spinal cord injury (5,7). Such hypothesis was supported by the findings that tissue levels of HNE have also been shown to be increased after spinal cord injury (SCI) (8,9). However, similar measurements of acrolein in SCI have not accomplished.…”
Section: Introductionmentioning
confidence: 93%
“…However, subsequent studies using one of the more contemporary rat contusion SCI paradigms and more sensitive immunoblotting of the immunohistochemical assay methods have more completely and specifically defined the time course of LP (4-HNE, acrolein) and protein oxidation (protein carbonyl), and nitration (3-NT) following SCI. The first of these showed a peak increase in 4-HNE immunostaining at 24 h [21] or 48 h [20] after SCI. A more recent and more extended immunoblotting/immunohistochemical time course study in the rat contusion model has confirmed that the increase in 4-HNE occurs as early as 1 h, peaks at 24 h, and remains significantly elevated for at least 7 days [23].…”
Section: Onset and Duration Of Oxidative Damage In The Injured Spinalmentioning
confidence: 99%
“…An increase in LP that appears in the injured cord within the first hour has also been evidenced in terms of a depletion of endogenous antioxidants, including ascorbic acid [16], alpha-tocopherol (also known as vitamin E) [17], glutathione [18], and ubiquinol-9 and ubiqunol-10 [19]. More contemporary immunohistochemical and immunoblotting methods have been recently used, which reveals an impressive increase in the levels of the LP-derived aldehydic breakdown products 4-HNE [20][21][22][23] and acrolein [24,25].…”
Section: Increased Lipid Peroxidationmentioning
confidence: 99%
“…The role of reactive oxygen-induced oxidative damage to spinal cord lipids (i.e., lipid peroxidation, LP) and proteins following acute spinal cord injury (SCI) has been strongly supported in previous work (Aksenova et al, 2002; Baldwin et al, 1998; Braughler and Hall, 1989; Hall and Braughler, 1993; Juurlink and Paterson, 1998; Springer et al, 1997). Earlier investigations attributed much of the post-traumatic oxidative damage to the reactive oxygen species (ROS) hydrogen peroxide (H 2 O 2 ) and its derived hydroxyl radical (•OH) formed rapidly by iron-dependent Fenton reactions (Braughler and Hall, 1989).…”
Section: Introductionmentioning
confidence: 82%